Review on Performance Analysis of Multipath Fading Channels - Ch.Padmaja, N.Swathi, Ch.Sridevi (International Journal of Advanced Science and Technology, 2020)
Multipath fading effects the link performances in Cellular and wireless communications. Link performance has to be analyzed using different digital modulation schemes under various fading channels. In this paper, we analyze the proper uses of Rician and Rayleigh fading channels. Simulation results for link performance obtained using these channel modeling in binary phase shift keying (BPSK) Quadrature phase shift keying (QPSK) and M-ary phase shift keying (MPSK) systems correspond closely to the theoretical results. Simulation results are shown that to understand the effect of fading channels with different digital modulation schemes and use to verify the best suitable fading channels expressed in terms of bit error rate (BER) and symbol error rate (SER) performances.